Relationship between Study Habit and Academic Achievement of Secondary School Students in Oyo State - OYASOLA, Samuel Olalekan; ADEGOKE, Adebare Idowu (Ilorin Journal of Education, 2023)
The study investigated the relationship between study habit and academic achievement in among biology students: a case study of secondary school students in Oyo state. The study employed a descriptive correlational research design. The sample for the study consists of 200 students was drawn from a total population 1,270 using random sampling procedure across eight senior secondary schools from four local government areas in Oyo state purposely used for the study. Two research instruments for data collection were used. Questionnaire titled Science Students Study Habit Questionnaire (SSSHAQ and Broad Sheet of Academic Performance (BSAP)). Three hypotheses were tested. The results were analyzed using Pearson Product Moment Correlation was used to test hypothesis formulated at 0.05 level of significance. The results revealed that there is positive significant relationship between study habit and academic performance of senior secondary school students in the study area as it enhances their academic performance on both public and private schools. Also, it was revealed that significant difference exist between male and female secondary students in their study habit and academic achievement. The study concluded that school counselors, tutors, and parents have a responsibility to ensure that students develop good study habits for hard work and confidence in both private and public schools